Late Survival After Aortic Valve Replacement in Patients With Moderately Reduced Kidney Function - Natalie Glaser; Veronica Jackson; Martin J. Holzmann; Anders Franco‐Cereceda; Ulrik Sartipy (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The influence of moderately reduced kidney function on late survival after surgical aortic valve replacement (AVR) is unknown. We analyzed survival after AVR in patients with moderately reduced kidney function. Methods and Results All patients who underwent primary AVR in Sweden 1997–2013 were identified from the Swedish Web system for Enhancement and Development of Evidence‐based care in Heart disease Evaluated According to Recommended Therapies register. Patients were categorized according to estimated glomerular filtration rate (eGFR). Of 13 102 patients, 9836 (75%) had normal kidney function (eGFR >60 mL/min per 1.73 m2) and 3266 (25%) had moderately reduced kidney function (eGFR 30–60 mL/min per 1.73 m2). Mean follow‐up time was 6.2 years. Mortality was higher in patients with moderately reduced kidney function; 5‐, 10‐, and 15‐year survival was 76%, 48%, and 25% versus 89%, 73%, and 55% (adjusted hazard ratio [HR], 1.28; 95% CI, 1.18–1.38; P<0.001). Patients with moderately reduced kidney function had a nonsignificantly higher risk of major bleeding (HR, 1.18; 95% CI, 1.00–1.39; P=0.051) and a lower risk for aortic valve reoperation (HR, 0.54; 95% CI, 0.38–0.79; P=0.001) compared to those with normal kidney function. In patients with moderately reduced kidney function, survival was similar in those who received bioprostheses compared to those who received mechanical valves (HR, 0.85; 95% CI, 0.70–1.03; P=0.094). Conclusions Moderately reduced kidney function was strongly associated with increased mortality after AVR. These results have important implications for preoperative risk stratification, and suggest that patients with eGFR 30 to 60 mL/min per 1.73 m2 warrant careful observation after AVR. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT02276950.